1972
DOI: 10.1037/h0032319
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in a three-person Prisoner's Dilemma.

Abstract: Subjects played either a standard two-person Prisoner's Dilemma game or an equivalent three-person version. Despite the fact that an economic model would predict equal rates of cooperation, triads were substantially less cooperative. The transition matrices indicated that it was more difficult in the threeperson setting to establish a pattern of cooperation that could be subsequently maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 7 publications
3
40
0
Order By: Relevance
“…Hence, in larger groups persons should feel less constraint against behaving in a self-interested way for the short term. Prior studies assessing the effect of group size indeed do report somewhat less cooperation in larger groups (Bixenstine et al, 1966;Bonacich, Shure, Kahan and Meeker, 1976;Hamburger, Guyer and Fox, 1975;Komorita and Lapworth, 1982;Marwell and Schmidt, 1972). However, in these studies the range of group size is relatively small (up to nine persons).…”
Section: Structural Mechanisms That Affect Decision-makingmentioning
confidence: 87%
“…Hence, in larger groups persons should feel less constraint against behaving in a self-interested way for the short term. Prior studies assessing the effect of group size indeed do report somewhat less cooperation in larger groups (Bixenstine et al, 1966;Bonacich, Shure, Kahan and Meeker, 1976;Hamburger, Guyer and Fox, 1975;Komorita and Lapworth, 1982;Marwell and Schmidt, 1972). However, in these studies the range of group size is relatively small (up to nine persons).…”
Section: Structural Mechanisms That Affect Decision-makingmentioning
confidence: 87%
“…One is based on the idea that a number of factors conducive to cooperation, such as social pressure and social incentives, may be more effective in small than larger groups (Olson 1965). Other authors (Marwell and Schmitt 1972) have suggested the 'bad apple' hypothesis. Many individuals are willing to cooperate, but only as long as others do so as well.…”
Section: Introductionmentioning
confidence: 99%
“…See Ledyard (1995) and Chaudhuri (2011) for reviews of experiments using this framework. 2 Marwell and Schmitt (1972) compare two-and three-person prisoner's dilemma games, while Bonacich et al (1976) study three-, six-and nine-person games. In both studies payoff matrices are chosen so that cooperating rather than defecting decreases own payoff, and increases total payoff, by the same amount across games.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the positive side, it was noted that the &ee rider hypothesis tends to be supported as group size increases (Dawes et al, 1977;Marwell and Schmidt, 1972).…”
Section: Game Theoiy and Public Goodsmentioning
confidence: 96%